Progression-free and overall survival in patients with recurrent Glioblastoma multiforme treated with last-line bevacizumab versus bevacizumab/lomustine - Heiland, Dieter Henrik; Masalha, W.; Franco, P.; Machein, M. R.; Weyerbrock, A. (Journal of Neuro-Oncology, 2016)
Bevacizumab (BEV) is widely used for treatment of patients with recurrent glioblastoma multiforme (GBM). 1-(2-Chlorethyl)-cyclohexyl-nitrosourea (CCNU, lomustine) monotherapy is an approved chemotherapeutical option for recurrent GBM. Recent evidence demonstrated a survival benefit of combined treatment with BEV and CCNU in patients with a first recurrence of GBM. We examined the outcome of recurrent GBM patients with BEV monotherapy versus BEV/CCNU therapy when used as last-line therapy. 35 patients with recurrent GBM treated between 2010 and 2014 were included in this retrospective study. Progression-free and overall survival was determined with reference to the beginning of BEV or BEV/CCNU therapy and initial diagnosis. 17 patients received BEV monotherapy, 18 patients received combined BEV and CCNU therapy. The impact of parameters such as IDH mutation, MGMT promoter methylation, tumor localization, histology and the number of surgeries were included in a multivariate ANOVA analysis. Furthermore, Karnofsky performance score (KPS), neurological function and toxicity were assessed. BEV/CCNU treatment led to an extension of PFS (6.11 months; 95 % CL 3.41–12.98 months; log-rank p = 0.00241) and OS (6.59 months; 95 % CL 5.51–16.3 months; log-rank p = 0.0238) of 2 months compared to BEV monotherapy. This survival advantage was independent of histology, IDH mutation status or the number of previous surgeries. Neurological function, KPS and toxicity were not significantly different between both treatment groups. Last-line therapy with BEV/CCNU results in a longer PFS and OS compared to BEV monotherapy and is well-tolerated. These findings confirm the role of these agents in the treatment of recurrent GBM and are in line with other studies.
CRIS-Team Scopus Importer:2024-03-07
Keywords: Bevacizumab; CCNU; Glioblastoma multiforme; Last-line therapy; Tumor recurrence